Assessing the needs of healthcare providers to comply with the Sindh Health Service Providers and Facilities Act (2021) on violence prevention in Karachi, Pakistan. - Ali, Syeda Tabeena; Muffadil, Tasneem; Yasir, Muhammad; Otho, Muhammad Suleman; Siddiqui, Muhammad Bilal (International Journal of Endorsing Health Science Research, 2024)
Background: Workplace violence against healthcare providers is a serious issue in Pakistan. In 2021, the Government of Sindh enacted legislation titled “The Sindh Health Service Providers and Facilities (Prevention of Violence and Damage to Property) Act” to address this problem. This study aimed to assess the needs of healthcare providers in complying with this Act. Methodology: A cross-sectional quantitative survey was conducted among 384 healthcare providers in emergency departments of selected public and private hospitals in Karachi. Data was collected using a structured questionnaire and analyzed using descriptive and inferential statistics. Results: Significant gaps were identified in implementing security measures, incident reporting systems, staff training, and collaboration with law agencies, indicating the need for improvement. Key challenges reported were lack of resources, ethical issues in reporting, and inadequate response by authorities. Conclusion: Targeted strategies are required to enhance healthcare providers’ capacity in compliance with the Violence Prevention Act. Priorities include policy dissemination, infrastructure upgrades, streamlined reporting and referral pathways, and training healthcare staff on legal rights and response protocols. Effective implementation of the Act can promote healthcare staff safety and delivery of quality care.